Effect of laser frequency and focal length on copper surface temperature during laser heating - Yus Erny Amirah, Mohd Yusof; Muhammad Afiq, Ahmad; Aiman, M. H.; Moinuddin, Mohammed Quazi; Mahadzir, Ishak (Springer Singapore, 2022)
Laser heating is a process that uses laser as a heat source. In this paper, the copper surface temperature during the laser heating process was studied by controlling the laser frequency and focal length. The laser heating experiment was conducted using a fiber laser marking machine and irradiated with a constant 27 W laser power within a duration of 51 s. The laser frequency and focal length were varied from 100 to 300 kHz and −3 cm to +3 cm, respectively. Meanwhile, laser surface modification (LSM) was performed on the copper rod surface to enhance the laser energy absorption. Furthermore, the defocusing modes for laser heating were used to analyze the variation of temperature. The focus point of the focal length for this experiment was set up at 18.4 cm from the focal plane and denoted as 0. Laser frequency and focal length were found to play an important role in increasing the surface temperature during laser heating since it affects the heat input delivered to the materials. It was found that the surface temperature reaches a higher degree, 879.2 °C with the combination of 200 kHz laser frequency at focal length 0